A versatile one-dimensional numerical model for packed-bed heat storage systems. (April 2019) - Esence, Thibaut; Bruch, Arnaud; Fourmigué, Jean-François; Stutz, Benoit
Abstract: Thanks to their versatility and their relatively low cost, packed-bed sensible heat storage systems are promising for various applications like in concentrated solar power plants, adiabatic compressed energy storage and pumped thermal energy storage. A versatile one-dimensional numerical model able to describe many packed-bed configurations is developed and presented. This model is able to treat liquid and gaseous heat transfer fluids, and packed bed with a monomodal or a bimodal particle size repartion, i.e. consisting of a mixture of large and small solid particles (such as rocks and sand). This configuration is commonly encountered in the literature due to the advantages it procures. The model is compared and validated with specific experimental data and results from the literature covering wide ranges of configurations and operating conditions: several heat transfer fluids (molten salts, thermal oil, air), solid materials (rocks, sand, ceramics), fluid velocities, temperature levels and packed bed configurations are successfully tested. This shows the versatility of the developed model. The influence of the fluid velocity on heat losses, thermal diffusion and fluid/solid heat exchange are analysed. It enables to determine the optimal velocity which maximizes the performance of the storage system. Highlights: Description of a versatile numerical model for packed-bed heat storage systems. Relevant approaches and correlations to compute a priori heat transfer coefficients. Validation of the model in various configurations with experimental data. Utilization of the model to investigate the fluid velocity influence.